EFL LEARNERS’ LEARNING STYLE PREFERENCES IN RELATION TO THEIR ENGLISH PROFICIENCY - Manan, Siti Saleha; Suhartini, Lelly; Muhsin, Muh. Khusnun (Universitas Halu Oleo, 2019)
The aim of this study was to find out students’ learning stylepreference and its correlation with their English Proficiency. Theresearch questions were as follows (1) what are the most preferredlearning styles of EFL Learner at English Department? (2) Is thereany significant correlation between students’ learning stylepreferences and their English Proficiency? The study usedCorrelation design. The number of sample in this study was 35students from English department of Halu Oleo University in theacademic year who had followed TOEFL test. The data werecollected using questionnaire which adopted Perceptual Learning-Style Preference Questionnaire (PLSPQ), developed by John Reid(1987) consisting of 30 statements and student’s TOEFL score. Thedata of this study were analyzed through descriptive statistic andLinear Regression Analysis. The results showed that (1) majorlearning style were tactile learning style and kinesthetic learningstyle (2) The coefficient correlation was 0.070 which was greaterthan 0.05 (level of significance). It means that there was nocorrelation between students’ learning style and their Englishproficiency.Keywords: Student’s Learning Style, English Proficiency.